Early Years of the Journal of Learning for Development: A Combination of Bibliometrics and Thematic Analysis - Sanjaya Mishra (Commonwealth of Learning, 2019)
The paper analyses the contributions to Journal of Learning for Development (JL4D) from volume one to five using bibliometrics and content analysis techniques. Analysing the 91 papers in various categories of JL4D, the paper identifies authorship pattern, topics covered, research methods used, types of documents used in citations, core journals and the median age of citations to JL4D. The finding of the study reveals that JL4D has created a niche for itself as a specialised research journal focusing on innovations in learning contributing to development.